2007
DOI: 10.1007/s10529-007-9318-5
|View full text |Cite
|
Sign up to set email alerts
|

A phosphate starvation-induced acid phosphatase from Oryza sativa: phosphate regulation and transgenic expression

Abstract: A phosphate starvation-induced acid phosphatase cDNA was cloned from the rice, Oryza sativa. The cDNA encoding O. sativa acid phosphatase (OsACP1) has 1100 bp with an open reading frame of 274 amino acid residues. The deduced amino acid sequence of OsACP1 cDNA showed 53% identity to tomato acid phosphatase and 46-50% identity to several other plant phosphatases. OsACP1 expression was up-regulated in the rice plant and in cell culture in the absence of phosphate (Pi). The induced expression of OsACP1 was a spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Several studies have reported that overexpression of secreted PAPs can improve plant biomass and Pi accumulation (Xiao et al, 2006;Hur et al, 2007;Ma et al, 2009;Wang et al, 2009). However, these attempts have either focused around high-specificity phytases or PAPs with extracellular roles, but unclear intracellular function.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that overexpression of secreted PAPs can improve plant biomass and Pi accumulation (Xiao et al, 2006;Hur et al, 2007;Ma et al, 2009;Wang et al, 2009). However, these attempts have either focused around high-specificity phytases or PAPs with extracellular roles, but unclear intracellular function.…”
Section: Resultsmentioning
confidence: 99%
“…APases catalyze the cleavage of Pi from phosphate esters under acidic conditions. Both intracellular and secreted APases are induced during Pi deficiency (Baldwin et al 2001;Hur et al 2007;Wang et al 2014). Intracellular APases are involved in recycling and remobilizing Pi from senescent tissue, while secreted APases are involved in scavenging of Pi from organic sources in the external environment (Robinson et al 2012a, b;Tian et al 2012;Vance et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Purple acid phosphatases (PAPs) form a unique group among the APases, characterized by the purple color of the purified protein in aqueous solution and an iron (III)-containing dimetal center in the catalytic site (Olczak et al 2003;Strater et al 1995). PAPs have been found in, and characterized from, many plant species, including Arabidopsis, rice, tobacco, sweet potato, kidney bean and soybean, as well as other crop plants (Dionisio et al 2011;Durmus et al 1999;Hur et al 2007;Kaida et al 2003;Li et al 2002;Liang et al 2012;Liang 1998;Schenk et al 1999). PAPs contain five conserved amino acid motifs required for metal binding: DXG/GDXXY/GNH[D/E]/VXXH/ GHXH (bold letters represent the metal-binding residues) (Li et al 2002;Schenk et al 2000;Strater et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, our recent results indicated that rice acid phosphatase (OsACP1) is up-regulated specifically during P i starvation and is functionally expressed in transgenic Arabidopsis. This finding suggests that the OsACP1 gene can be used to develop new transgenic dicotyledonous plants that are able to adapt to P i -deficient conditions (Hur et al 2007).…”
Section: Introductionmentioning
confidence: 93%